The Effect of Policy on Changes in Final Income Tax Rates on MSME Taxpayer Compliance in Binjai City - Amelia Putri; Nuri Aslami (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Taxes are one of the sources of state revenue, the government sets taxpayers to the public, especially MSME taxes, looking for sectors that have the potential to increase tax revenue. . This study aims to analyze the effect of changes in the PPH tax rate on MSME taxpayer compliance. This study uses qualitative research methods, with an empirical juridical approach. This study shows the existence of a policy regarding the MSME income tax rate of 1% through Government Regulation no. 46 of 2013. However, the enactment of this regulation experienced pros and cons among the public. As a result, in 2018 the government changed the tax rate by 0.5% through Government Regulation no. 23 of 2018. This policy on reducing income tax rates for MSMEs has an impact on MSME compliance levels as taxpayers. Research conducted at the Binjai Pratama Tax Service Office shows an increase in the compliance of MSME actors in carrying out their tax obligations, so it can be interpreted that the implementation of PP 46 of 2013 provides a significant increase in the efficiency of fulfilling tax obligations for taxpayers at KPP Pratama Binjai.